Production process of micro-fine denier bi-component sheath-core high-quality composite fiber
Through the production process of fine denier two-component leather core high-quality composite fibers, the problems of insufficient fiber absorption, breathability and softness in the prior art are solved, and fiber performance with efficient moisture absorption, quick drying and high comfort are achieved.
Patent Information
- Application Number
- CN202411422748.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to meet the multifunctional and high-quality needs of high-end sanitary napkins and diapers for fibers, especially in terms of moisture absorption, breathability and softness.
The production process of fine denier two-component leather core high-quality composite fibers is adopted, and PET particles are treated by plasma discharge to synthesize pyramidal chitosan, and porous fibers are formed by hot melt blowing and drafting processes, and single-construction is constructed by combining polylactic acid film. Guide wet fiber.
It improves the moisture absorption and quick-drying performance, softness and antibacterial effect of the fiber, enhances the specific surface area and capillary force of the fiber, and improves the overall performance of the product.
Smart Images

Figure BDA0005081301330000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fibers, in particular to a production process of micro-denier two-component sheath-core high-quality composite fibers. Background Art
[0002] With the increase of per capita disposable income, the change of parenting concepts, and the improvement of quality of life, people's consumption needs are constantly changing, and the demand for high-quality, high-end products and differentiated products is also increasing. People's demands for multi-functionality and high quality of sanitary napkins, diapers and other products are gradually increasing, such as "dryness", "breathability", "softness and non-irritation", etc., which also puts higher requirements on the performance and quality of raw materials of products, driving the expansion of fiber demand. Non-woven fabrics made of ES fiber have good comfort and are ideal materials for manufacturing high-end sanitary napkins and diapers. They are in line with the development trend of high-end consumption and have good development prospects. Summary of the invention
[0003] The purpose of the present invention is to provide a production process for fine denier two-component sheath-core high-quality composite fibers to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: A production process of fine denier two-component sheath-core high-quality composite fiber, comprising the following process steps:
[0005] (1) treating high melting point PET particles by plasma discharge for 60 to 300 seconds to obtain hydrophilic PET particles;
[0006] (2) Add chlorogenic acid solution dropwise to 10-20 g / L chitosan solution, the molar ratio of chlorogenic acid to chitosan is 0.75-2:1, stir at 60 rpm for 40 min in an ice water bath, continue stirring in a dark place at room temperature for 24 h, add 3-octenoic acid, the molar ratio of 3-octenoic acid to chitosan is 1-1.5:1, continue stirring for 0.5-2 h, then centrifuge at 10000 r / min for 20 min, and freeze-dry the supernatant at -18°C for 24 h to obtain amphiphilic chitosan;
[0007] (3) The three-stage temperature of the torque rheometer is adjusted to 125-140° C., the rheometer is preheated to the set temperature, 45 g of low melting point polyethylene, 5-20 g of amphiphilic chitosan, 0.05-0.1 g of diisopropylbenzene peroxide, and 0.22 g of antioxidant 300# are quickly added to the mixing tank, and a melt grafting reaction is carried out at a speed of 30-50 r / min to obtain modified polyethylene;
[0008] (4) conveying the skin layer melt and the core layer melt to a melt metering pump through respective pipelines, the metering pump speed is 10-80 r / min, and then conveying them to a skin-core type bicomponent spinning assembly, extruding a thin stream of melt from the skin-core spinneret hole at 275-290° C., and cooling and forming under the action of side blowing at 15-20° C., 5-6 kPa, and 72-96 m / min to obtain a skin-core fiber;
[0009] (5) Add 10-20% polylactic acid-dichloromethane solution and N-methylpyrrolidone in a mass ratio
[0010] 1:0.005-0.008, and stir evenly to obtain polylactic acid slurry; completely immerse the core-skin fiber in the polylactic acid slurry for 1-15 minutes to obtain polylactic acid / skin-core fiber;
[0011] (6) After baking the polylactic acid / skin-core fiber at 100° C. for 2 h, the fiber is subjected to secondary drawing, wherein the primary drawing ratio is 3 to 9 times and the secondary drawing ratio is 2 to 4 times. After the drawing is completed, the fiber is completely immersed in water for 0.5 to 2 h, and then sodium hydroxide is added to a concentration of 0.001 to 0.01 mol / L. The fiber is immersed at 30 to 60° C. for 0.5 to 5 min, taken out, and dried at 80° C. for 24 h to obtain a porous fiber.
[0012] (7) Dodecylsilane, n-hexane, and water were mixed in a volume ratio of 1:20:0.02 to obtain a dodecylsilane solution. The porous fiber was immersed in the dodecylsilane solution for 30 seconds, taken out, washed three times with ethanol and distilled water in sequence, and dried at 80°C for 24 hours to obtain a fine denier two-component core-skin high-quality composite fiber.
[0013] Furthermore, the melting point of the high melting point PET particles in step (1) is 250-260°C.
[0014] Furthermore, the plasma discharge treatment in step (1) is carried out by using argon / oxygen mixed plasma with an argon gas flow rate of 10 cm 3 / min, oxygen flow rate is 30cm 3 / min, and the plasma discharge power is 100-200W.
[0015] Furthermore, the solvent in the chitosan solution of step (2) is 2% by volume acetic acid aqueous solution, and the relative molecular mass of chitosan is 5.0×10 4 .
[0016] Furthermore, in step (2), the chlorogenic acid solution is as follows: 0.5-0.7 g of chlorogenic acid, 0.1-0.2 g of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 20 mL of 70% ethanol aqueous solution are stirred and dissolved, and then 0.16 g of N-hydroxysuccinimide is added to an ice water bath and stirred at 60 rpm for 1 hour.
[0017] Furthermore, the melting point of the low-melting-point polyethylene in step (3) is 110-125°C.
[0018] Furthermore, in step (4), the sheath-core ratio of the sheath-core fiber is 2-4:6-8.
[0019] Furthermore, in step (4), the skin layer melt is prepared by adding 100 parts by mass of modified polyethylene completely melted at 130-140°C, and then adding 10-50 parts by mass of sodium chloride and 10-20 parts by mass of modified medical stone, and stirring and mixing; the core layer melt is prepared by completely melting hydrophilic PET particles at 275-290°C.
[0020] Furthermore, the modified medical stone is prepared by modifying medical stone nano-crushed material with coupling agent KH-171, and the average particle size of the medical stone nano-crushed material is ≤15nm.
[0021] Furthermore, the porous fiber in step (4) has a fineness of 0.55 dtex, a porosity of 50-60%, and an average pore size of 5-100 μm.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] (1) The present invention uses hydrophilic modified high melting point PET as the core layer and modified polyethylene as the skin layer, and adds sodium chloride and nano fillers to the skin layer for hot melt spinning to initially obtain skin-core fibers. With continuous stretching and thinning, the particles inside the skin layer gradually present a convex structure on the fiber surface, thereby roughening the fiber surface and obtaining a higher specific surface area. At the same time, due to the difference in compatibility between sodium chloride and polyethylene during hot melt spinning, interface micropores are generated, stretching micropores are formed during the stretching process, and dissolution micropores are completely dissolved during the water extraction and washing process, thereby obtaining porous skin-core fibers, which are expected to improve the moisture absorption and quick-drying properties of the fibers;
[0024] (2) The present invention uses a core-skin fiber and a polylactic acid film to construct a unidirectional moisture-conducting fiber, thereby increasing the softness and comfort of the fiber and achieving the effects of moisture absorption and antibacterial. After the stretching is completed, the fiber is immersed in water to dissolve the porogen in the hydrophobic polylactic acid film, so that micropores appear on the surface of the film. As the micropores appear, water penetrates into the modified polyethylene cortex and further dissolves the porogen in the cortex. At this time, sodium hydroxide is added to adjust the sodium hydroxide concentration in the water, thereby activating the PET layer and causing micropores to appear. The fiber obtained by the present invention has an appropriate amount of micropores distributed therein, and some of the micropores are connected. In addition, the high specific surface area can generate additional capillary force, which is expected to increase the moisture absorption rate and greatly increase the contact area with the remaining air, thereby enhancing the moisture absorption and moisture conduction performance of the fiber and the water diffusion rate.
[0025] (3) The present invention uses chlorogenic acid, 3-octenoic acid and chitosan to react, and adjusts the ratio of the three, so that chlorogenic acid and 3-octenoic acid are grafted on the amino group of chitosan, so that chitosan has both hydrophilic groups and hydrophobic long chains, and finally obtains amphiphilic chitosan, and then uses the amphiphilic chitosan to graft into the polyethylene molecular chain to achieve the hydrophilic-hydrophobic dual effect of the cortex, while improving the antibacterial property of the cortex, thereby improving the antibacterial effect of the fiber, and then the polylactic acid film is hydrophobically modified, so that the fiber presents a hydrophilic, hydrophilic-hydrophobic, and hydrophobic gradient wettability change process from the inside to the surface, which greatly enhances the additional pressure of the fiber on water, so that water is spontaneously transferred from the hydrophobic surface to the hydrophilic interior, so that water is directional transported, thereby enabling the fiber to be used in sanitary napkins, diapers and other medical and health materials. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] Example 1; (1) The high melting point PET particles were subjected to plasma discharge treatment for 180s to obtain hydrophilic PET particles; the plasma discharge treatment: using argon / oxygen mixed plasma, the argon flow rate was 10cm 3 / min, oxygen flow rate is 30cm 3 / min, plasma discharge power is 200W;
[0028] (2) After 0.5 g of chlorogenic acid, 0.1 g of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 20 mL of 70% ethanol aqueous solution were stirred and dissolved, 0.16 g of N-hydroxysuccinimide was added and placed in an ice water bath, and the mixture was stirred at 60 rpm for 1 h to obtain a chlorogenic acid solution; a 5.0×10 4 Chitosan was dissolved in an acetic acid aqueous solution with a volume fraction of 2% to obtain a 10 g / L chitosan solution, and then a chlorogenic acid solution was added dropwise, the molar ratio of chlorogenic acid to chitosan was 0.75:1, and the mixture was stirred at 60 rpm for 40 min in an ice water bath, and continued to stir in a dark place at room temperature for 24 h, and 3-octenoic acid was added, the molar ratio of 3-octenoic acid to chitosan was 1:1, and continued to stir for 0.5 h, and then centrifuged at 10000 r / min for 20 min, and the supernatant was freeze-dried at -18°C for 24 h to obtain amphiphilic chitosan;
[0029] (3) The three-stage temperature of the torque rheometer is adjusted to 135° C. The rheometer is preheated to the set temperature, and 45 g of low melting point polyethylene, 5 g of amphiphilic chitosan, 0.1 g of diisopropylbenzene peroxide, and 0.22 g of antioxidant 300# are quickly added to the mixing tank, and a melt grafting reaction is carried out at a speed of 40 r / min to obtain modified polyethylene;
[0030] (4) After 100 parts by weight of modified polyethylene is completely melted at 140° C., 10 parts by weight of sodium chloride and 10 parts by weight of modified medical stone are added, and the mixture is stirred and mixed to obtain a skin layer melt; the hydrophilic PET particles are used as the core layer melt and the skin layer melt are transported to a melt metering pump through respective pipelines, the metering pump speed is 55 r / min, and then the melt is sent to a skin-core type two-component spinning assembly, and a thin stream of the melt is extruded from the skin-core spinneret hole at 280° C., and the melt is cooled and formed under the action of a side blow at 15° C., 5 kPa, and 82 m / min, with a skin-core ratio of 2:8, to obtain a skin-core fiber; the modified medical stone is prepared from a nano-crushed medical stone modified by a coupling agent KH-171, and the average particle size of the nano-crushed medical stone is 10 nm;
[0031] (5) mixing a 10% polylactic acid-dichloromethane solution and N-methylpyrrolidone in a mass ratio of 1:0.005, and stirring to obtain a polylactic acid slurry; completely immersing the sheath-core fiber in the polylactic acid slurry for 5 minutes to obtain a polylactic acid / sheath-core fiber;
[0032] (6) After baking the polylactic acid / skin-core fiber at 100° C. for 2 h, the fiber was subjected to secondary stretching, wherein the primary stretching ratio was 6 times and the secondary stretching ratio was 2.5 times. After the stretching was completed, the fiber was completely immersed in water for 1 h, sodium hydroxide was added to a concentration of 0.01 mol / L, and the fiber was immersed at 45° C. for 2 min, taken out, and dried at 80° C. for 24 h to obtain a porous fiber; the porous fiber had a porosity of 55% and an average pore size of 65 μm;
[0033] (7) Dodecylsilane, n-hexane, and water were mixed in a volume ratio of 1:20:0.02 to obtain a dodecylsilane solution. The porous fiber was immersed in the dodecylsilane solution for 30 seconds, taken out, washed three times with ethanol and distilled water in sequence, and dried at 80°C for 24 hours to obtain a fine denier two-component core-skin high-quality composite fiber.
[0034] Example 2; (1) The high melting point PET particles were subjected to plasma discharge treatment for 180s to obtain hydrophilic PET particles; the plasma discharge treatment: using argon / oxygen mixed plasma, the argon flow rate was 10cm 3 / min, oxygen flow rate is 30cm 3 / min, plasma discharge power is 200W;
[0035] (2) After 0.6 g of chlorogenic acid, 0.1 g of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 20 mL of 70% ethanol aqueous solution were stirred and dissolved, 0.16 g of N-hydroxysuccinimide was added and placed in an ice water bath, and the mixture was stirred at 60 rpm for 1 h to obtain a chlorogenic acid solution; a 5.0×10 4 Chitosan was dissolved in an acetic acid aqueous solution with a volume fraction of 2% to obtain a 15 g / L chitosan solution, and then a chlorogenic acid solution was added dropwise, the molar ratio of chlorogenic acid to chitosan was 1.1:1, and the mixture was stirred at 60 rpm for 40 min in an ice water bath, and continued to stir in a dark place at room temperature for 24 h, and 3-octenoic acid was added, the molar ratio of 3-octenoic acid to chitosan was 1.2:1, and continued to stir for 0.5 h, and then centrifuged at 10000 r / min for 20 min, and the supernatant was freeze-dried at -18°C for 24 h to obtain amphiphilic chitosan;
[0036] (3) The three-stage temperature of the torque rheometer is adjusted to 135° C. The rheometer is preheated to the set temperature, and 45 g of low melting point polyethylene, 14 g of amphiphilic chitosan, 0.1 g of diisopropylbenzene peroxide, and 0.22 g of antioxidant 300# are quickly added to the mixing tank, and a melt grafting reaction is carried out at a speed of 40 r / min to obtain modified polyethylene;
[0037] (4) After 100 parts by weight of modified polyethylene is completely melted at 140° C., 30 parts by weight of sodium chloride and 15 parts by weight of modified medical stone are added, and the mixture is stirred and mixed to obtain a skin layer melt; the hydrophilic PET particles are used as the core layer melt and the skin layer melt are transported to a melt metering pump through respective pipelines, the metering pump speed is 55 r / min, and then the melt is sent to a skin-core type two-component spinning assembly, and a thin stream of the melt is extruded from the skin-core spinneret hole at 280° C., and the melt is cooled and formed under the action of a side blowing of 15° C., 5 kPa, and 82 m / min, with a skin-core ratio of 4:6, to obtain a skin-core fiber; the modified medical stone is prepared from a nano-crushed medical stone modified by a coupling agent KH-171, and the average particle size of the nano-crushed medical stone is 10 nm;
[0038] (5) mixing a polylactic acid-dichloromethane solution with a mass fraction of 10 to 20% and N-methylpyrrolidone in a mass ratio of 1:0.005 to 0.008, and stirring to obtain a polylactic acid slurry; completely immersing the sheath-core fiber in the polylactic acid slurry for 5 minutes to obtain a polylactic acid / sheath-core fiber;
[0039] (6) After the polylactic acid / skin-core fiber is baked at 100° C. for 2 hours, it is subjected to secondary stretching, wherein the primary stretching ratio is 6 times and the secondary stretching ratio is 2.5 times. After the stretching is completed, the fiber is completely immersed in water. After soaking for 1 hour, sodium hydroxide is added to a concentration of 0.01 mol / L, and the fiber is soaked at 45° C. for 2 minutes. The fiber is taken out and dried at 80° C. for 24 hours to obtain a porous fiber; the porous fiber has a porosity of 58% and an average pore size of 62 μm;
[0040] (7) Dodecylsilane, n-hexane, and water were mixed in a volume ratio of 1:20:0.02 to obtain a dodecylsilane solution. The porous fiber was immersed in the dodecylsilane solution for 30 seconds, taken out, washed three times with ethanol and distilled water in sequence, and dried at 80°C for 24 hours to obtain a fine denier two-component core-skin high-quality composite fiber.
[0041] Example 3; (1) The high melting point PET particles were subjected to plasma discharge treatment for 180s to obtain hydrophilic PET particles; the plasma discharge treatment: using argon / oxygen mixed plasma, the argon flow rate was 10cm 3 / min, oxygen flow rate is 30cm 3 / min, plasma discharge power is 200W;
[0042] (2) After 0.7 g of chlorogenic acid, 0.1 g of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 20 mL of 70% ethanol aqueous solution were stirred and dissolved, 0.16 g of N-hydroxysuccinimide was added and placed in an ice water bath, and the mixture was stirred at 60 rpm for 1 h to obtain a chlorogenic acid solution; a 5.0×10 4Chitosan was dissolved in an acetic acid aqueous solution with a volume fraction of 2% to obtain a 20 g / L chitosan solution, and then a chlorogenic acid solution was added dropwise, the molar ratio of chlorogenic acid to chitosan was 2:1, and the mixture was stirred at 60 rpm for 40 min in an ice water bath, and continued to stir in a dark place at room temperature for 24 h, and 3-octenoic acid was added, the molar ratio of 3-octenoic acid to chitosan was 1.5:1, and continued to stir for 0.5 h, and then centrifuged at 10000 r / min for 20 min, and the supernatant was freeze-dried at -18°C for 24 h to obtain amphiphilic chitosan;
[0043] (3) The three-stage temperature of the torque rheometer is adjusted to 135° C. The rheometer is preheated to the set temperature, and 45 g of low melting point polyethylene, 20 g of amphiphilic chitosan, 0.1 g of diisopropylbenzene peroxide, and 0.22 g of antioxidant 300# are quickly added to the mixing tank, and a melt grafting reaction is carried out at a speed of 40 r / min to obtain modified polyethylene;
[0044] (4) After 100 parts by weight of modified polyethylene is completely melted at 140° C., 50 parts by weight of sodium chloride and 20 parts by weight of modified medical stone are added, and the mixture is stirred and mixed to obtain a skin layer melt; the hydrophilic PET particles are used as the core layer melt and the skin layer melt are transported to a melt metering pump through respective pipelines, the metering pump speed is 55 r / min, and then the melt is sent to a skin-core type two-component spinning assembly, and a thin stream of melt is extruded from the skin-core spinneret hole at 280° C., and the melt is cooled and formed under the action of a side blowing of 15° C., 5 kPa, and 82 m / min, and the skin-core ratio is 2:8, thereby obtaining a skin-core fiber; the modified medical stone is prepared from a nano-crushed medical stone modified by a coupling agent KH-171, and the average particle size of the nano-crushed medical stone is 10 nm;
[0045] (5) mixing a 20% by mass polylactic acid-dichloromethane solution and N-methylpyrrolidone in a mass ratio of 1:0.008, and stirring to obtain a polylactic acid slurry; completely immersing the sheath-core fiber in the polylactic acid slurry for 5 minutes to obtain a polylactic acid / sheath-core fiber;
[0046] (6) After baking the polylactic acid / skin-core fiber at 100° C. for 2 h, the fiber was subjected to secondary stretching, wherein the primary stretching ratio was 6 times and the secondary stretching ratio was 2.5 times. After the stretching was completed, the fiber was completely immersed in water for 1 h, sodium hydroxide was added to a concentration of 0.01 mol / L, and the fiber was immersed at 45° C. for 2 min, taken out, and dried at 80° C. for 24 h to obtain a porous fiber; the porous fiber had a porosity of 60% and an average pore size of 70 μm;
[0047] (7) Dodecylsilane, n-hexane, and water were mixed in a volume ratio of 1:20:0.02 to obtain a dodecylsilane solution. The porous fiber was immersed in the dodecylsilane solution for 30 seconds, taken out, washed three times with ethanol and distilled water in sequence, and dried at 80°C for 24 hours to obtain a fine denier two-component core-skin high-quality composite fiber.
[0048] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the high melting point PET particles are not subjected to plasma discharge treatment, and the remaining steps are the same as Example 1.
[0049] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that chlorogenic acid is not added, and the remaining steps are the same as Example 1.
[0050] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that 3-octenoic acid is not added, and the remaining steps are the same as Example 1.
[0051] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that sodium chloride is not added, and the remaining steps are the same as Example 1.
[0052] Comparative Example 5; The difference between Comparative Example 5 and Example 1 is that N-methylpyrrolidone is not added, and the remaining steps are the same as Example 1.
[0053] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that modified medical stone is not added, and the remaining steps are the same as Example 1.
[0054] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is that sodium hydroxide is not added, and the remaining steps are the same as Example 1.
[0055] Comparative Example 8: The difference between Comparative Example 8 and Example 1 is that the porous fiber is not immersed in the dodecylsilane solution, and the remaining steps are the same as Example 1.
[0056] Application performance testing:
[0057] In order to better test the unidirectional moisture conductivity and moisture absorption and quick-drying properties of the fiber prepared in the present invention, the fibers prepared in the above specific examples 1 to 3 and comparative examples 1 to 8 of the present invention were selected to prepare a fiber having a gram weight of 40 g / m 2 Non-woven fabrics. The unidirectional moisture conduction test refers to AATCC195-2009 "Liquid Moisture Management Performance of Textiles" to test the unidirectional transmission index (MMT) of the fabric, which characterizes the unidirectional transmission ability of the fabric and is divided into 1 to 5 levels, among which 5 is the best, and those above 3 are considered to have unidirectional moisture conduction effect. The moisture absorption and quick-drying test refers to GB / T21655.1-2008 "Evaluation of Moisture Absorption and Quick-drying Properties of Textiles". The antibacterial rate test refers to AATCC100-1996, antibacterial rate = (blank control sample live bacteria count - non-woven fabric live bacteria count) / blank control sample live bacteria count, where the blank control sample uses pure cotton cloth, and the test results are shown in Table 1.
[0058] Table 1 Analysis results of unidirectional moisture conductivity and moisture absorption and quick-drying properties of micro-denier two-component sheath-core high-quality composite fibers
[0059]
[0060] The present invention adopts a skin-core fiber and a hydrophobic polylactic acid film with a wettability gradient change, which greatly enhances the additional pressure of the fiber on water, so that water is spontaneously transferred from the hydrophobic surface to the hydrophilic interior, and the water is directional transported. Then, the water-soluble principle is used to elute and dissolve the porogen in the skin layer and the film layer to form a porous structure, and sodium hydroxide is used to further activate the core layer material, so that micropores are distributed in the three layers inside the fiber, forming a capillary channel, and improving the moisture absorption and quick-drying performance of the fiber.
[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. The production process of micro-denier two-component sheath-core high-quality composite fiber is characterized by: The process steps include: (1) treating high melting point PET particles by plasma discharge for 60 to 300 seconds to obtain hydrophilic PET particles; (2) Add chlorogenic acid solution dropwise to 10-20 g / L chitosan solution, the molar ratio of chlorogenic acid to chitosan is 0.75-2:1, stir at 60 rpm for 40 min in an ice water bath, continue stirring in a dark place at room temperature for 24 h, add 3-octenoic acid, the molar ratio of 3-octenoic acid to chitosan is 1-1.5:1, continue stirring for 0.5-2 h, then centrifuge at 10000 r / min for 20 min, and freeze-dry the supernatant at -18°C for 24 h to obtain amphiphilic chitosan; (3) The three-stage temperature of the torque rheometer is adjusted to 125-140° C., the rheometer is preheated to the set temperature, 45 g of low melting point polyethylene, 5-20 g of amphiphilic chitosan, 0.05-0.1 g of diisopropylbenzene peroxide, and 0.22 g of antioxidant 300# are quickly added to the mixing tank, and a melt grafting reaction is carried out at a speed of 30-50 r / min to obtain modified polyethylene; (4) conveying the skin layer melt and the core layer melt to a melt metering pump through respective pipelines, the metering pump speed is 10-80 r / min, and then conveying them to a skin-core type bicomponent spinning assembly, extruding a thin stream of melt from the skin-core spinneret hole at 275-290° C., and cooling and forming under the action of side blowing at 15-20° C., 5-6 kPa, and 72-96 m / min to obtain a skin-core fiber; (5) mixing a polylactic acid-dichloromethane solution with a mass fraction of 10 to 20% and N-methylpyrrolidone in a mass ratio of 1:0.005 to 0.008, and stirring to obtain a polylactic acid slurry; completely immersing the sheath-core fiber in the polylactic acid slurry for 1 to 15 minutes to obtain a polylactic acid / sheath-core fiber; (6) After baking the polylactic acid / skin-core fiber at 100° C. for 2 h, the fiber is subjected to secondary drawing, wherein the primary drawing ratio is 3 to 9 times and the secondary drawing ratio is 2 to 4 times. After the drawing is completed, the fiber is completely immersed in water for 0.5 to 2 h, and then sodium hydroxide is added to a concentration of 0.001 to 0.01 mol / L. The fiber is immersed at 30 to 60° C. for 0.5 to 5 min, taken out, and dried at 80° C. for 24 h to obtain a porous fiber. (7) Dodecylsilane, n-hexane, and water were mixed in a volume ratio of 1:20:0.02 to obtain a dodecylsilane solution. The porous fiber was immersed in the dodecylsilane solution for 30 seconds, taken out, washed three times with ethanol and distilled water in sequence, and dried at 80°C for 24 hours to obtain a fine denier two-component core-skin high-quality composite fiber.
2. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: The melting point of the high melting point PET particles in step (1) is 250-260°C.
3. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: Step (1) The plasma discharge treatment: using argon / oxygen mixed plasma, the argon flow rate is 10cm 3 / min, oxygen flow rate is 30cm 3 / min, and the plasma discharge power is 100-200W.
4. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: The solvent in the chitosan solution of step (2) is 2% by volume acetic acid aqueous solution, and the relative molecular mass of chitosan is 5.0×10 4 .
5. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: Step (2) The chlorogenic acid solution: 0.5-0.7 g of chlorogenic acid, 0.1-0.2 g of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 20 mL of 70% ethanol aqueous solution were stirred to dissolve, and then 0.16 g of N-hydroxysuccinimide was added to an ice water bath and stirred at 60 rpm for 1 h.
6. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: The melting point of the low-melting-point polyethylene in step (3) is 110-125°C.
7. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: The sheath-core ratio of the sheath-core fiber in step (4) is 2-4:6-8.
8. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: The skin layer melt of step (4) is prepared by adding 100 parts by mass of modified polyethylene completely melted at 130-140°C, and then adding 10-50 parts by mass of sodium chloride and 10-20 parts by mass of modified medical stone, and stirring and mixing; the core layer melt is prepared by completely melting hydrophilic PET particles at 275-290°C.
9. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 8, characterized in that: The modified medical stone is prepared by modifying medical stone nano-crushed material with coupling agent KH-171, and the average particle size of the medical stone nano-crushed material is ≤15nm.
10. The production process of the micro-denier two-component core-skin high-quality composite fiber according to claim 1, characterized in that: The porous fiber in step (4) has a fineness of 0.55 dtex, a porosity of 50-60%, and an average pore size of 5-100 μm.
Citation Information
Cited By
One-way moisture absorption and heat preservation composite fiber for fabric and preparation method thereof
CN121931640A